Altered mRNA Expression of Genes Involved in Endocannabinoid Signalling in Squamous Cell Carcinoma of the Oral Tongue. (14th September 2019) - Alhouayek, Mireille; Boldrup, Linda; Fowler, Christopher J.
Abstract: Little is known about the endocannabinoid (eCB) system in squamous cell carcinoma of the oral tongue (SCCOT). Here we have investigated, at the mRNA level, expression of genes coding for the components of the eCB system in tumour and non-malignant samples from SCCOT patients. Expression of NAPEPLD and PLA2G4E, coding for eCB anabolic enzymes, was higher in the tumour tissue than in non-malignant tissue. Among genes coding for eCB catabolic enzymes, expression of MGLL was lower in tumour tissue while PTGS2 was increased. It is concluded that the eCB system may be dysfunctional in SCCOT.